2016
DOI: 10.1016/j.socscimed.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Taking the bull by the horns: Ethical considerations in the design and implementation of an Ebola virus therapy trial

Abstract: Ebola virus is categorized as one of the most dangerous pathogens in the world. Although there is no known cure for Ebola virus, there is some evidence that the severity of the disease can be curtailed using plasma from survivors. Although there is a general consensus on the importance of research, methodological and ethical challenges for conducting research in an emergency situation have been identified. Performing clinical trials is important, especially for health conditions that are of public health signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Reasons for participation in medical research in general have been widely documented. [ 8 , 45 59 ] A specificity of this intervention, however, lies in the recruitment of survivors as participants for plasma donation and not as trial patients, leading to new ethical questions surrounding the use of CP before trial implementation [ 3 , 60 ]. To the best of our knowledge, no ethical guidelines existed for survivors providing an experimental product before the start of a trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for participation in medical research in general have been widely documented. [ 8 , 45 59 ] A specificity of this intervention, however, lies in the recruitment of survivors as participants for plasma donation and not as trial patients, leading to new ethical questions surrounding the use of CP before trial implementation [ 3 , 60 ]. To the best of our knowledge, no ethical guidelines existed for survivors providing an experimental product before the start of a trial.…”
Section: Discussionmentioning
confidence: 99%
“…This gap was partially filled by the conception of WHO guidelines on the use of Convalescent Blood and Plasma [ 3 , 27 , 61 , 62 ] that advised considering the CP donors as research participants, similar to the CP recipients. This logic was followed in Ebola-Tx, hereby extending the risks and benefits from EVD patients to the CP donors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al [73] Ethical and social solutions identified (Table 4) The temporal and spatial variation in the risk of infection during outbreaks presents not only statistical hurdles but also an ethical challenge for study designs [75]. Previous research responses have highlighted the many challenges in agreeing on simultaneously ethical, scientifically valid and acceptable study designs [18,36,42,51,59,64,66], addressing socially valuable questions [14,18,64,66]. The exclusion of children and pregnant women was an ethical concern during the Ebola outbreak in LMICs [18,69], compounded by challenges of obtaining complex consent [2, 4, 5, 15, 18, 21, 25, 32, 34, 44-46, 50, 69, 70].…”
Section: Disseminationmentioning
confidence: 99%
“…Le déploiement de la recherche clinique de la MVE épidémique répond à une nécessité scientifique et une obligation morale. Sa mise en place a décliné l'adossement à une exigence éthique [85,86]. Deux exemples en sont l'illustration, celui de : l'administration de la note d'information et de la réception du consentement éclairé et ; celui de la faisabilité (en contexte hostile et d'urgence sanitaire) de la réalisation du tirage au sort entre groupe intervention et groupe comparateur sans intervention au cours d'un essai comparatif randomisé et sans dérogation exceptionnelle de recours au médicament évalué hors essai.…”
Section: Figureunclassified